Nomadic memories: autonomy, territory and gentrification. The dispute for the center of Madrid - Sánchez Llorca, Ana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The text alludes to how the construction of memory about collective self-organization processes, such as expressions of resistance to the process of gentrification and touristificationinitiated in the center of Madrid (Spain) between 1997 and 2003 and until the present day, has generated powerful dissidence among the inhabitants. This is based on documental and iconographical material located in the archive of the Centro Social El Laboratorio, as well as in the voices found in the fabric of the community in the Lavapiés neighborhood (Madrid), in the struggle for the rights to the city, which implies adebate between tradition and modernity. This allows us to appreciate how memory in the context of a territory constructs and reconfigures based on lived experiences and conflicts, and how the memory of resistance in itself becomes a way to debate both the past and present literature regarding the territory. In this way, it is intended to problematize the ways of looking at the past, as well as the way of thinking and imagining «other» forms of social organization.